Second GHEP-ISFG exercise for DVI: "DNA-led" victims' identification in a simulated air crash. (July 2021) - Vullo, Carlos M.; Catelli, Laura; Ibarra Rodriguez, Adriana A.; Papaioannou, Aikaterini; Merino, J. Carlos Álvarez; Lopez-Parra, AM; Gaviria, Aníbal; Baeza-Richer, Carlos; Romanini, Carola; González-Moya, Esperanza; Casals, Ferran; Calafell, Francesc; et al.
Abstract: The Spanish and Portuguese-Speaking Working Group of the International Society for Forensic Genetics (GHEP-ISFG) has organized a second collaborative exercise on a simulated case of Disaster Victim Identification (DVI), with the participation of eighteen laboratories. The exercise focused on the analysis of a simulated plane crash case of medium-size resulting in 66 victims with varying degrees of fragmentation of the bodies (with commingled remains). As an additional difficulty, this second exercise included 21 related victims belonging to 6 families among the 66 missings to be identified. A total number of 228 post-mortem samples were represented with aSTR and mtDNA profiles, with a proportion of partial aSTR profiles simulating charred remains. To perform the exercise, participants were provided with aSTR and mtDNA data of 51 reference pedigrees —some of which deficient—including 128 donors for identification purposes. The exercise consisted firstly in the comparison of the post-mortem genetic profiles in order to re-associate fragmented remains to the same individual and secondly in the identification of the re-associated remains by comparing aSTR and mtDNA profiles with reference pedigrees using pre-established thresholds to report a positive identification. Regarding the results of the post-mortem samples re-associations, only a small number of discrepancies among participants were detected, all of which were from just a few labs. However, in the identification process by kinship analysis with family references, there were more discrepancies in comparison to the correct results. The identification results of single victims yielded fewer problems than the identification of multiple related victims within the same family groups. Several reasons for the discrepant results were detected: a) the identity/non-identity hypotheses were sometimes wrongly expressed in the likelihood ratio calculations, b) some laboratories failed to use all family references to report the DNA match, c) In families with several related victims, some laboratories firstly identified some victims and then unnecessarily used their genetic information to identify the remaining victims within the family, d) some laboratories did not correctly use "prior odds" values for the Bayesian treatment of the episode for both post-mortem/post-mortem re-associations as well as the ante-mortem/post-mortem comparisons to evaluate the probability of identity. For some of the above reasons, certain laboratories failed to identify some victims. This simulated "DNA-led" identification exercise may help forensic genetic laboratories to gain experience and expertize for DVI or MPI in using genetic data and comparing their own results with the ones in this collaborative exercise. Highlights: The GHEP-ISFG has designed a second "DNA-led" DVI exercise in a simulated air crash. This exercise can be useful for testing DVI using the data and results provided. The exercise is focused on direct matching and kinship analysis in a Bayesian framework. This exercise sheds light on problems that a laboratory can face in DVI scenarios.